Pharmacological classification of centrally acting drugs using EEG in freely moving rats: an old tool to identify new atypical dopamine uptake inhibitors. (15th December 2019) - Zanettini, Claudio; Scaglione, Alessandro; Keighron, Jacqueline D.; Giancola, JoLynn B.; Lin, Shih-Chieh; Newman, Amy H.; Tanda, Gianluigi
Abstract: Atypical dopamine uptake inhibitors (DUIs) bind to the dopamine transporter and inhibit the reuptake of dopamine but have lower abuse potential than psychostimulants. Several atypical DUIs can block abuse-related effects of cocaine and methamphetamine, thus making them potential medication candidates for psychostimulant use disorders. The aim of the current study is to establish an in-vivo assay using EEG for the rapid identification of atypical DUIs with potential for medication development. The typical DUIs cocaine and methylphenidate dose-dependently decreased the power of the alpha, beta, and gamma bands. The atypical DUI modafinil and its F-analog, JBG1-049, decreased the power of beta, but in contrast to cocaine, none of the other frequency bands, while JHW007 did not significantly alter the EEG spectrum. The mu-opioid receptor agonists heroin and morphine dose-dependently decreased the power of gamma and increased power of the other bands. The effect of morphine on EEG power bands was antagonized by naltrexone. The NMDA receptor antagonist ketamine increased the power of all frequency bands. Therefore, typical and atypical DUIs and drugs of other classes differentially affected EEG spectra, showing distinctive features in the magnitude and direction of their effects on EEG. Comparative analysis of the effects of test drugs on EEG indicates a potential atypical profile of JBG1-049 with similar potency and effectiveness to its parent compound modafinil. These data suggest that EEG can be used to rapidly screen compounds for potential activity at specific pharmacological targets and provide valuable information for guiding the early stages of drug development. This article is part of the issue entitled 'Special Issue on Neurotransmitter Transporters'. Highlights: Atypical dopamine uptake inhibitors (DUIs) are candidate pharmacotherapies for psychostimulant use disorders. Typical and atypical DUIs, as well as centrally active drugs from other classes, produce distinct EEG neurosignatures. EEG can be used for the early identification of dopamine uptake inhibitors with an atypical profile.